Exo-Functionalized Metallacages as Host-Guest Systems for the Anticancer Drug Cisplatin - Woods, Ben; Wenzel, Margot N.; Williams, Thomas; Thomas, Sophie R.; Jenkins, Robert L.; Casini, Angela (Frontiers in Chemistry, 2019)
Within the framework of designing new self-assembled metallosupramolecular architectures for drug delivery, seven [Pd2L4]4+ metallacages (L = 2,6-bis(pyridine-3-ylethynyl)pyridine) featuring different groups in exo-position, selected to enhance the cage solubility in aqueous environment, were synthesized. Thus, carboxylic acids, sugars and PEG groups were tethered to the bispyridyl ligands directly or via disulfide bond formation, as well as via click chemistry. The ligands and respective cages were characterized by different methods, including NMR spectroscopy and high-resolution electrospray mass spectrometry (HR-ESI-MS). While the two ligands featuring carboxylic acid-functionalized groups showed improved solubility in water, the other ligands were soluble only in organic solvents. Unfortunately, all the respective self-assembled cages were also insoluble in water. Afterwards, the encapsulation properties of the anticancer drug cisplatin in selected [Pd2L4]X4 cages (X = NO3- , BF4-) were studied by 1H, 1H DOSY and 195Pt NMR spectroscopy. The effect of the counter ions as well as of the polarity of the solvent in the drug encapsulation process were also investigated, and provided useful information on the host-guest properties of these experimental drug delivery systems. Our results provide further experimental support for previous studies that suggest the desolvation of guests from surrounding solvent molecules and the resulting solvent rearrangement may actually be the primary driving force for determining guest binding affinities in metallacages, in the absence of specific functional group interactions.